Relationship between tumorigenesis, metastasis, immune evasion, and chemoresistance in osteosarcoma therapy - Yan Yik Lim, Ahmad Mujahid Ahmad Zaidi, Mainul Haque, Azizi Miskon (Journal of Applied Pharmaceutical Science, 2024)
There has been no significant efficacy in treating osteosarcoma (OS) metastasis after nearly four decades of trials. This motivates us to elucidate OS therapies using their four bidirectional mutation stages. The historical developments and clinical advancements are briefly described to refresh the OS therapy status quo. However, the main issue of metastasis remains unresolved, accounting for 90% of pulmonary metastasis deaths. Thus, this metastasis problem is related to immune evasion and chemoresistance induced after long-term treatment by immunotherapy for tumorigenesis. Therefore, it is rational to discuss the relationship cycles of mutation stages, including tumorigenesis, metastasis, immune evasion, and chemoresistance. Even though many combinational and targeted therapies have been developed to intensify these mutation treatments, successful clinical translations with higher cure rates are still rare. Through this review, an in-depth understanding of the bidirectional relationship between the four OS mutation stages and their respective therapies is provided. Herein, we summarise the medicines for treating tumorigenesis, including Collagen beta (1-O) galactosyl transferase 2 inhibitors, transformer 2β, and ArfGAP with GTPase domain 1, miR-148a and miR-21-5p extracellular vesicles, and the long non-coding RNA leukemia inhibitory factor receptor antisense RNA1. Following the medicines for treating metastasis are AXL receptor tyrosine kinase, miR-135a-5p, messenger RNA B-cell lymphoma-6, transforming growth factor beta 1, T-cell immunoglobulin, and mucin-domain containing protein-3, suppressor of cytokine signalling-5, cancer susceptibility 15, Krüppel-like factor 3 antisense RNA 1, programmed cell death 4, autophagy-related gene 5, and Rab22a-NeoF1. Then the medicines for treating immune evasion are N-cadherin, ubiquitin-specific peptidase 12 inhibitors, latency-associated peptide domain inhibitors, anti-Wnt2 mAb, anti-αvβ8 integrin, hexokinase-2-mediated i-kappa-b-alpha, indoleamine 2,3-dioxygenase inhibitor with NO, and TGF-βRII with anti-IgG1. Finally, the medicines for treating chemoresistance are Dihydrofolate reductase, folylpoly-γ-glutamate synthetase, heat shock protein-90AA1, XCT-790, anlotinib tyrosine kinase inhibitor, and insulin-like growth factors 1. As a result, this contribution is expected to serve as a reference and guide for scientists and clinicians.
Keywords: Osteosarcoma, tumorigenesis, metastasis, immune evasion, chemoresistance, mutation